Carbapenemase-producing Enterobacterales in hospital drains in Southern Ontario, Canada. Issue 4 (December 2020) - Jamal, A.J.; Mataseje, L.F.; Brown, K.A.; Katz, K.; Johnstone, J.; Muller, M.P.; Allen, V.G.; Borgia, S.; Boyd, D.A.; Ciccotelli, W.; Delibasic, K.; Fisman, D.N.; et al.
Summary: Background: Hospital drains may be an important reservoir for carbapenemase-producing Enterobacterales (CPE). Aim: To determine prevalence of CPE in hospital drains exposed to inpatients with CPE, relatedness of drain and patient CPE, and risk factors for drain contamination. Methods: Sink and shower drains in patient rooms and communal shower rooms exposed to 310 inpatients with CPE colonization/infection were cultured at 10 hospitals. Using short- and long-read whole-genome sequencing, inpatient and corresponding drain CPE were compared. Risk factors for drain contamination were assessed using multi-level modelling. Findings: Of 1209 exposed patient room and communal shower room drains, 53 (4%) yielded 62 CPE isolates in seven (70%) hospitals. Of 49 CPE isolates in patient room drains, four (8%) were linked to prior room occupants. Linked drain/room occupant pairs included Citrobacter freundii ST18 isolates separated by eight single nucleotide variants (SNVs), related bla KPC -containing IncN3-type plasmids (different species), related bla KPC-3 -containing IncN-type plasmids (different species), and related bla OXA-48 -containing IncL/M-type plasmids (different species). In one hospital, drain isolates from eight rooms on two units were Enterobacter hormaechei separated by 0–6 SNVs. Shower drains were more likely to be CPE-contaminated than hand hygiene (odds ratio: 3.45; 95% confidence interval: 1.66–7.16) or patient-use (13.0; 4.29–39.1) sink drains. Hand hygiene sink drains were more likely to be CPE-contaminated than patient-use sink drains (3.75; 1.17–12.0). Conclusion: Drain contamination was uncommon but widely dispersed. Drain CPE unrelated to patient exposure suggests contamination by undetected colonized patients or retrograde (drain-to-drain) contamination. Drain types had different contamination risks.